Do Trade Frictions Distort the Purchasing Power Parity (PPP) Hypothesis? A Closer Look - Lumengo Bonga-Bonga (International Journal of Financial Studies, 2025)
This paper investigates whether trade frictions, in the form of exchange controls, are among the main obstacles preventing the Purchasing Power Parity (PPP) hypothesis from being valid among trading nations. It specifically looks at whether exchange controls—a type of trade friction—hinder PPP’s applicability in the relationship between an emerging economy, South Africa, and its major trading partners, classified by their use of exchange control regulations. The methodology used to test the PPP hypothesis includes nonlinearity through quantile unit root tests and quantile cointegration, designed to capture the varied economic conditions across trading nations. The empirical findings indicate that trade frictions may not necessarily obstruct the validity of the PPP hypothesis. Moreover, the weak form of the PPP hypothesis predominantly appears at the extreme quantiles of the real exchange rate among trading nations, especially the lower quantile, which is associated with the real exchange rate depreciation of the South African economy. This insight is significant for both policymakers and investors.